A ternary eutectic solvent for cellulose nanocrystal production: exploring the recyclability and pre-pilot scale-up - Mariño, Mayra A.; Paredes, Maria G.; Martinez, Natalia; Millan, Daniela; Tapia, Ricardo A.; Ruiz, Domingo; Isaacs, Mauricio; Pavez, Paulina (Frontiers in Chemistry, 2023)
Deep eutectic solvents (DES) formed by choline chloride (ChCl); p-toluenesulfonic acid (pTSA) of stoichiometry ChCl:pTSA (1:1); (1:2), and its ternary eutectic mixtures with phosphoric acid (PA) 85% as additive (ChCl:pTSA:PA) were evaluated for cellulose nanocrystals (CNC) isolation. Initially, the hydrolytic efficiency to produce CNC of each DES was compared before and after adding phosphoric acid by Hammett acidity parameters and Gutmann Acceptor Number. Moreover, DES and reaction time were studied at 80 °C for CNC optimization. The nanomaterial characteristics were analyzed by Field Emission Scanning Electronic Microscopy (FESEM), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetric Analysis (TGA). The ternary eutectic mixture ChCl:pTSA:PA molar ratio (1:1:1.35) was chosen as a suitable recyclable ternary system at lab scale. A CNC yield of about 80% was obtained from hydrolysis of commercial cellulose in 5 cycles of recovery, but it dropped to 35% in a pre-pilot scaling. However, no variation in average size of the resulting CNC was observed (132±50 nm x 23±4 nm), which presented high thermal stability (Tmax 362 °C) and high crystallinity of about 80% after 3 hs. of reaction time.